Risk monetization : converting threats and opportunities into impact on project value - Koller, Glenn R. (Glenn Robert), 1951- (Taylor & Francis, 2012)
Risk Monetization: Converting Threats and Opportunities into Impact on Project Value addresses the organizational, political, cultural, and technical issues related to implementing a successful risk assessment, management, and monetization process. Suitable for readers in any organization or area of expertise, the book assumes no prior background in risk assessment, management, or monetization.With more than three decades of experience in risk-process implementation, the author first explains the benefits of the risk-monetization process and how risk matters are generally not handled properly.